Periphery‐Functionalized Porous Organic Cages. Issue 46 (6th October 2016) - Reiss, Paul S.; Little, Marc A.; Santolini, Valentina; Chong, Samantha Y.; Hasell, Tom; Jelfs, Kim E.; Briggs, Michael E.; Cooper, Andrew I.
Abstract: By synthesizing derivatives of a trans ‐1, 2‐diaminocyclohexane precursor, three new functionalized porous organic cages were prepared with different chemical functionalities on the cage periphery. The introduction of twelve methyl groups (CC16 ) resulted in frustration of the cage packing mode, which more than doubled the surface area compared to the parent cage, CC3 . The analogous installation of twelve hydroxyl groups provided an imine cage (CC17 ) that combines permanent porosity with the potential for post‐synthetic modification of the cage exterior. Finally, the incorporation of bulky dihydroethanoanthracene groups was found to direct self‐assembly towards the formation of a larger [8+12] cage, rather than the expected [4+6], cage molecule (CC18 ). However, CC18 was found to be non‐porous, most likely due to cage collapse upon desolvation. Abstract : Cage decorating : Imine porous organic cages that possess a range of chemical functionalities on the cage periphery were prepared. The use of different functionalized diamine precursors led to cage compounds of different sizes and porosities, including one cage with the potential for further post‐synthetic modification.